Channeling social protection programs for improved nutrition in Bangladesh - International Food Policy Research Institute (International Food Policy Research Institute, 2016)
Bangladesh has been making impressive strides in reducing hunger and undernutrition; nonetheless, nutrition remains a challenge for many households. At the Compact 2025 roundtable discussion on May 5, 2016 in Dhaka, over 100 stakeholders from various sectors had the opportunity to discuss how to accelerate progress by leveraging multiple sectors such as agriculture, gender, social protection, water, and sanitation. The importance of a multi-sectoral approach to accelerating progress in eradicating hunger and undernutrition was recently highlighted by a pilot initiative in Bangladesh, the Transfer Modality Research Initiative, which leveraged social protection programs to improve nutrition.